Probing polyoxometalate-protein interactions using molecular dynamics simulations - Solé-Daura, Albert; Goovaerts, Vincent; Stroobants, Karen; Absillis, Gregory; Jiménez-Lozano, Pablo; Poblet, Josep M.; Hirst, J.D.; Parac-Vogt, Tatjana; Carbó, Jorge J. (Wiley-VCH Verlag, 2016)
The molecular interactions between the Ce(IV)-substituted Keggin anion [PW11O39Ce(OH2)4]3- (CeK) and hen egg white lysozyme (HEWL), was investigated by molecular dynamics (MD) simulations. We compared the analysis of CeK with the Ce(IV)-substituted Keggin dimer [(PW11O39)2Ce]10- (CeK2) and the Zr(IV)-substituted Lindqvist anion [W5O18Zr(OH2)(OH)]3- (ZrL) in order to understand how POM features such as the shape, the size, the charge or the type of incorporated metal ion influence the POM···protein interactions. Simulations revealed two regions of the protein, in which the CeK anion interacts strongly: the cationic sites formed by Arg21 on one hand and by Arg45 and Arg68 on the other. The two sites can be related with the observed selectivity in the hydrolytic cleavage of HEWL. The POMs chiefly interact with the side chains of the positively charged (arginines and lysines) and the polar uncharged (tyrosines, serines and aspargines) residues via electrostatic attraction and hydrogen bonding with the oxygens of the POM framework. The CeK anion shows higher protein affinity than the CeK2 and ZrL anions, because it is less hydrophilic and it has the right size and shape for stablishing interactions with several residues simultaneously. The larger and more negatively charged CeK2 anion has a high solvent-accessible surface, which is sub-optimal for the interaction, while the smaller ZrL anion is highly hydrophilic and it cannot interact simultaneously with several residues so efficiently.